Mona of the manor a novel - Maupin, Armistead 1944- (Harper, an imprint of HarperCollinsPublishers, 2024)
"The long-awaited tenth novel in Maupin's beloved and bestselling Tales of the City series, Mona of the Manor follows the adventures of Mona Ramsey--now the widowed Lady of a glorious old manor in the Cotswolds--and her fabulous butler-slash-adopted-son Wilfred, as they work to help an American visitor who has gotten herself in trouble."
Keywords: Widows / Fiction; Manors / Fiction; Butlers / Fiction; Gay people / Fiction; City and town life / Fiction; Cotswold Hills (England) / Fiction; Veuves / Romans, nouvelles, etc; Elderly women / Fiction; Aristocracy / Fiction; Gay men / Fiction; Transsexuals / Fiction; Dwellings / Fiction; Entertaining / Fiction; Homicide / Fiction; Novels